2022
DOI: 10.1155/2022/2669114
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of ACOT2 Predicts Worse Overall Survival and Abnormal Lipid Metabolism: A Potential Target for Acute Myeloid Leukemia

Abstract: Acyl-CoA thioesterase (ACOT) plays a considerable role in lipid metabolism, which is closely related to the occurrence and development of cancer, nevertheless, its role has not been fully elucidated in acute myeloid leukemia (AML). To explore the role of ACOT2 in AML and to provide a potential therapeutic target for AML, the expression pattern of ACOT was investigated based on the TNMplot, Gene Expression Profiling Interactive Analysis (GEPIA), and Cancer Cell Line Encyclopedia (CCLE) database, and diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…5 B). Several other studies have demonstrated that Acot1 , Acot2 , Acot3 , Cyp4a10 , and Cyp4a14 are closely related to steatosis, inflammation, and liver fibrosis [ [23] , [24] , [25] , [26] , [27] , [28] ]. Thus, Acot1 , Cyp4a10 , and Cyp4a14 were selected for further validation by qPCR in the livers of both groups, with the expression of all three genes decreasing significantly in the hUC-MSC-treated group ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 B). Several other studies have demonstrated that Acot1 , Acot2 , Acot3 , Cyp4a10 , and Cyp4a14 are closely related to steatosis, inflammation, and liver fibrosis [ [23] , [24] , [25] , [26] , [27] , [28] ]. Thus, Acot1 , Cyp4a10 , and Cyp4a14 were selected for further validation by qPCR in the livers of both groups, with the expression of all three genes decreasing significantly in the hUC-MSC-treated group ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of Acot2 in the liver leads to increased oxidation of fatty acids in vivo. Recently, some researchers have predicted that an increase in Acot2 expression may be an important feature of abnormal lipid metabolism [ 25 ]. Another study indicated that high fructose corn syrup consumption significantly increases Acot2 and Acot3 expression in mice [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In acute myeloid leukemia (AML) of the blood system ( 49 , 50 ), ACOT 2 and ACOT 7 plays an important role in lipid metabolism such as fatty acid elongation and the biosynthesis of unsaturated fatty acids. Among them, ACOT 2 was up-regulated in AML cell lines, and its high expression predicted decreased overall survival and abnormal lipid metabolism during disease progression in AML.…”
Section: Progress Of Acots In Cancermentioning
confidence: 99%